Developing contents for t-learning — MADCE-TVD (2018)
The application of processes, methods and tools when developing software is key to the quality of the final product and in the case of development of educational content for t-learning is a prevailing need to define and select the most appropriate methods and / or methodologies Taking into account the characteristics of this type of content. This paper presents the model “MADCE-TVD — Agile Model of Educational Content Development for Digital Television”. This model is based on agile methodologies, values and principles, its application and adaptation, combining it with other useful engineering practices for the development of Educational contents for t-learning, covering the technical, pedagogical and personalization aspects that must be applied when constructing educational contents for this context.